Understanding the use of knowledge sharing tools - Lee, Angela Siew Hoong *; Wang, Shan; Yeoh, William; Ikasari, Novita (Taylor and Francis, 2020)
This paper investigates the drivers of the use of knowledge-sharing tools through the lens of task– technology fit (TTF), the role of social factors, and the cognitive and affective mechanisms. Data were collected from 294 knowledge workers and analyzed using partial least squares. This study found that cognition (i.e., perceived usefulness) and positive affect play an important role in mediating the effect of TTF, social influence, and trust on users’ behavioral intention. Interestingly, the role of negative affect as a mediator between sociotechnical factors and behavioral intention is considered not significant by the knowledge workers. This research has practical implications for organizations that are planning or reviewing their knowledge-sharing initiatives.